2021
DOI: 10.3390/molecules26061737
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Hepatoprotective Activity and Oxidative Stress Reduction of Rosmarinus officinalis L. Shoots Tincture in Rats with Experimentally Induced Hepatotoxicity

Abstract: Rosmarinus officinalis L. is a widely known species for its medicinal uses, that is also used as raw material for the food and cosmetic industry. The aim of the present study was to offer a novel perspective on the medicinal product originating from this species and to test its hepatoprotective activity. The tested sample consisted in a tincture obtained from the fresh young shoots. Compounds that are evaluated for this activity are polyphenols and terpenoids, that are identified and quantified by HPLC–UV–MS a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 49 publications
(84 reference statements)
1
29
0
1
Order By: Relevance
“…Of the plant diversity of this group, Lamiaceae (also known as Mint family) possess 236 genera with anapproximately identified of 7000 species, constituting the largest plant groups of MAPs (Gharib, 2006;Ramasubramania, 2012). Regarding the well-known and reputed species of MAPs, sage (S. officinalis) and rosemary (R. officinalis) are commonly studied for their chemical composition due to their significant uses in various fields (for sage : Okaiyeto et al, 2021;Ovidi et al, 2021;Jedidi et al, 2021; for rosemary: Lešnik et al, 2021;Nguyen et al, 2021;Ielciu et al, 2021). Essentialoil of sage is mainly characterized with 1,8-cineole, camphor, α-thujone, β-thujone, borneol, viridiflorol, an dmanool (Raal et al, 2007;Taarit et al, 2010), whilst α-pinene, 1,8-cineol, (+)-camphor, and piperitone are of the reported compounds for rosemary (Gachkar et al, 2007;Hussain et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Of the plant diversity of this group, Lamiaceae (also known as Mint family) possess 236 genera with anapproximately identified of 7000 species, constituting the largest plant groups of MAPs (Gharib, 2006;Ramasubramania, 2012). Regarding the well-known and reputed species of MAPs, sage (S. officinalis) and rosemary (R. officinalis) are commonly studied for their chemical composition due to their significant uses in various fields (for sage : Okaiyeto et al, 2021;Ovidi et al, 2021;Jedidi et al, 2021; for rosemary: Lešnik et al, 2021;Nguyen et al, 2021;Ielciu et al, 2021). Essentialoil of sage is mainly characterized with 1,8-cineole, camphor, α-thujone, β-thujone, borneol, viridiflorol, an dmanool (Raal et al, 2007;Taarit et al, 2010), whilst α-pinene, 1,8-cineol, (+)-camphor, and piperitone are of the reported compounds for rosemary (Gachkar et al, 2007;Hussain et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The in vitro antioxidant capacity of S. vulgaris extracts was evaluated by three different methods: 2,2-diphenyl-picrylhydrazil (DPPH●) scavenging assay, ferric-reducing antioxidant power (FRAP) and cupric ion reducing antioxidant capacity (CUPRAC) ( Table 9 ). The three used methods were chosen in order to bring arguments that prove the antioxidant capacity of tested samples by three different mechanisms [ 31 , 32 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Results of the TPA determination were expressed as mg caffeic acid equivalents (CAE)/g dried vegetal material and calculated using a caffeic acid calibration curve graph (R 2 = 0.9956). All these experiments were performed in triplicate [ 31 , 33 , 44 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A novel perspective in the exploitation of MAPs was represented by the paper of Ielciu and co-workers, in which fresh young shoots of Rosmarinus officinalis L. were macerated in 90% ethanol to obtain a tincture, which was tested against liver tissue damages [ 3 ]. The phytochemical analysis led to the identification and quantification of polyphenols and terpenes by HPLC–UV–MS and GC–MS, respectively.…”
mentioning
confidence: 99%